Teaching children: The weightiness of adopting practical approach to teaching children - Achmad Kholili (Universitas Islam Malang, 2020)
Teaching children still becomes a challenging task today and copying with that is quite necessary. Although the strategies have been implemented to be successful language learning for the children, however, it sometimes still fails due to lack of several practical approaches in the teaching process. This paper is presented to shed light on some practical approaches to teaching English to young learners. It covers intellectual development, attention span, sensory input, affective factors, and authentic meaningful language. These approaches are offered so as to make the goal of learning attainable. The teachers are strongly recommended to apply this in English language teaching to their children.